LINGUISTICS AT FERGANA STATE UNIVERSITY: PAST AND PRESENT (Scientific journal of the Fergana State University, 2025)
This article discusses the current state of linguistics in our republic, the contributions of scholars from Fergana in its development, and some scientific directions of linguistics at Fergana State University, along with their formation and progress. It also covers the scientific research conducted by university scholars during the independence period. In particular, it analyzes the work carried out in the fields of grammar, text syntax, stylistics, lexicology, dialectology, systemic linguistics, and some new directions in the science of linguistics.